Peacock pie - De la Mare, Walter John 1873-1956.; Ardizzone, Edward 1900-. (New York Knopf, 1961)
Presents a collection of poems first published in 1916 describing the capers of fairies, princes, beasts, children, witches, farmers, and kings.
Poems for children.
Keywords: English poetry